Internal Control over Financial Reporting and the Safeguarding of Corporate Resources: Evidence from the Value of Cash Holdings - Gao, Xinghua; Jia, Yonghong (Contemporary Accounting Research, 2016)
Abstract We test whether internal control weaknesses ( ICW s) endanger cash resources that manifests in a lower value of cash. Our results indicate that investors value liquid assets in ICW firms substantially less than they do in non‐ ICW firms. The negative valuation effect of weak internal control mainly concentrates on ICW s related to the control environment or overall financial reporting process. While firms remediating ICW s reverse the value loss from holding cash, firms whose internal control deteriorates or remains ineffective exhibit a lower value of cash. The marginal effect of ICW s on the value of cash remains significant after controlling for existing governance mechanisms and accounting conservatism, highlighting a unique governance role of internal control in mitigating unresolved agency problems and safeguarding corporate resources.